2017
DOI: 10.1038/srep44186
|View full text |Cite
|
Sign up to set email alerts
|

ENOblock, a unique small molecule inhibitor of the non-glycolytic functions of enolase, alleviates the symptoms of type 2 diabetes

Abstract: Type 2 diabetes mellitus (T2DM) significantly impacts on human health and patient numbers are predicted to rise. Discovering novel drugs and targets for treating T2DM is a research priority. In this study, we investigated targeting of the glycolysis enzyme, enolase, using the small molecule ENOblock, which binds enolase and modulates its non-glycolytic ‘moonlighting’ functions. In insulin-responsive cells ENOblock induced enolase nuclear translocation, where this enzyme acts as a transcriptional repressor. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 64 publications
(97 reference statements)
0
43
0
Order By: Relevance
“…Since the expression of about 48 kDa HA-tagged TgENO1 has been con rmed by western immunoblotting [31], it is expected that its N-terminal long form has migrated into the nucleus and has the capacity for binding to putative gene promoters to control gene expression during the intracellular proliferation of T. gondii [31]. Furthermore, Cho et al showed that ENOblock, a chemical probe for elucidating the moonlighting functions of ENO1, induces the nuclear localization of the long form of 48 kDa ENO1 [32]. It is generally considered that proteins with a molecular weight of about 40 kDa or larger cannot pass through the nuclear pore for their shuttling from the cytoplasm into the nucleoplasm.…”
Section: Discussionmentioning
confidence: 98%
“…Since the expression of about 48 kDa HA-tagged TgENO1 has been con rmed by western immunoblotting [31], it is expected that its N-terminal long form has migrated into the nucleus and has the capacity for binding to putative gene promoters to control gene expression during the intracellular proliferation of T. gondii [31]. Furthermore, Cho et al showed that ENOblock, a chemical probe for elucidating the moonlighting functions of ENO1, induces the nuclear localization of the long form of 48 kDa ENO1 [32]. It is generally considered that proteins with a molecular weight of about 40 kDa or larger cannot pass through the nuclear pore for their shuttling from the cytoplasm into the nucleoplasm.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, beta enolase, also a glycolytic protein, exhibited a greater decrease in adult vs. aged muscles with DFO. However, non-glycolytic functions of enolase related to repression of transcription have recently been identified [ 70 ]. Since enolase is not believed to play a major regulatory role (i.e., a rate-limiting step) in glycolysis [ 71 ], the changes observed here may be more related to these non-glycolytic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Since enolase is not believed to play a major regulatory role (i.e., a rate-limiting step) in glycolysis [ 71 ], the changes observed here may be more related to these non-glycolytic functions. Future work could examine changes in beta enolase localization, which has been linked to glycolytic vs. non-glycolytic function [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 d after freezing, cryosections were taken at a 7 µm thickness (Leica CM1850). Masson's trichrome staining was performed using the previously published protocol 71 . Microscopic images were obtained at 25× magnification and the thickness of the left ventricle was measured using Image J 1.48 v software (National Institutes of Health).…”
Section: Echocardiography Cardiac Functional Indices Were Obtained Umentioning
confidence: 99%